LA DESIGNAZIONE DELL’AREA CROMATICA DEL GRIGIO NEI DIALETTI ITALIANI - CUGNO, Federica; CUSAN, Federica (Studia Universitatis Babeș-Bolyai Philologia, 2022)
The Designation of the Chromatic Area of Grey in Italian Dialects. This article aims to study aspects of lexicalisation relating to the formation and usage of names designating ‘dark grey’ and ‘light grey’ in Italian dialects collected by the Italian Linguistic Atlas. These terms exist on the margins of the system of colour names present in dialects, and therefore the listing and analysis of the data allow us to note an interesting variety of linguistic solutions which compensate for the lack of a precise corresponding term in the dialect. From a geolinguistic point of view, the mapping of the data allows us to distinguish between shared areas covering the whole of Italy, and linguistic or cultural sub-areas with more specific features. Article history: Received 16 July 2021; Revised 22 October 2021; Accepted 20 November 2021; Available online 31 March 2022; Available print 31 March 2022. REZUMAT. Desemnarea zonei cromatice a griului în dialectele italiene. Acest articol își propune să studieze aspectele lexicalizării privitoare la formarea și la utilizarea denumirilor pentru „gri-închis” și „gri-deschis” în dialectele italiene, excerptate din Atlasul Lingvistic Italian. Acești termeni se află la periferia sistemului numelui de culori prezent în dialecte și, prin urmare, lista și analiza lor ne permit să observăm o varietate interesantă de soluții lingvistice care compensează lipsa unui termen dialectal corespunzător. Din punct de vedere geolingvistic, cartografierea datelor face posibilă distincția dintre zonele comune, care acoperă întreaga Italie, și subzonele lingvistice sau culturale ce au trăsături, adesea, particulare. Cuvinte-cheie: nume de culori, dialecte italiene, Atlante Linguistico Italiano, gri-închis, gri-deschis